Pelatihan pengolahan PMT Puding Tinggi Protein pada kader Posyandu sebagai upaya pencegahan balita gizi kurang di Kelurahan Plaju - Windi Indah Fajar Ningsih; Sari Bema Ramdika; Fatria Harwanto; Ardesy Melizah Kurniati (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
The implementation of posyandu activities cannot be separated from the role of cadres. One of the cadres' tasks is to manage the provision of PMT for toddlers participating in posyandu. Plaju is included in the 10 areas with the highest population density in Palembang City with problems of malnutrition and stunting still being found. Proper provision of PMT can improve the nutritional status of toddlers in order to achieve optimal growth and development in toddlers. The problems in providing PMT are the nutritional content that is not yet dense in nutrition, lack of variety and boredom in the PMT menu. Therefore, it is necessary to provide assistance to cadres to be able to process PMT that is more varied, high in protein and appropriate and tastes that toddlers like, such as pudding. This community service activity was carried out on 25 cadres from 5 posyandus in Plaju involving 4 lecturers and 8 students. the activity was carried out in September 2024. The success of the activity will be evaluated through the results of the pretest and posttest. The level of cadre knowledge regarding high-protein PMT and the cadre's ability to process high-protein PMT through a high-protein pudding creation competition